Hamlet, Pirates, and Purgatory - Rutter, Tom (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
Hamlet’s abduction by pirates during his voyage to England is an episode that does not appear in the main narrative source of Shakespeare’s play, Belleforest’s Histoires tragiques. This essay surveys the various sources that have been proposed, including the Ur-Hamlet, Plutarch’s “Life of Julius Caesar,” and an event in the biography of Martin Luther, before proposing a further possibility in the form of a sermon by the Swiss theologian Heinrich Bullinger where purgatory is compared to pirate capture. It discusses the likelihood of Shakespeare encountering this sermon directly or indirectly, and then argues that reading Hamlet in the light of it has important implications for our understanding of the relationship between the prince, his father, and Claudius.